Behcet’s disease in a patient with primary sclerosing cholangitis: a case report and literature review - Bielecka-Kowalska, Natalia P.; Lewkowicz, Natalia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Behçet’s disease (BD) is a rare, chronic multisystem disease of unknown aetiology. Clinically, it presents with ulceration located on the oral and genital mucosa, skin, uveitis, arthritis and neurological disorders. Most commonly, the disease affects men in the second and third decades of life and occurs endemically. The vast majority of cases have been reported in Asia and the Mediterranean area. The diagnosis of this disease is difficult, especially because of its rare occurrence in Central Europe. In this report, we present the case of BD in a 56-year-old man with primary sclerosing cholangitis, followed by a literature review covering current insights into BD aetiology, diagnostics and treatment.